2002
DOI: 10.1016/s0370-2693(02)01817-8
|View full text |Cite
|
Sign up to set email alerts
|

Zeroes of the neutrino mass matrix

Abstract: We assume there to be precisely three left-handed neutrino states whose Majorana masses are generated by an unspecified mechanism. Were CP conserved, the symmetric neutrino mass matrix M would be real and all six of its distinct entries could be experimentally determined. But CP is not conserved so that M is likely to be complex. As a result, not all nine of its convention-independent real parameters can be determined without an appeal to theory. Thus we examine the possibility that a restricted class of neutr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
548
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 388 publications
(579 citation statements)
references
References 4 publications
29
548
2
Order By: Relevance
“…Apart from being interesting in itself, several scalar triplets naturally occur in models for neutrino masses and lepton mixing based on the type II seesaw mechanism. In particular, it has been shown that in such a scenario a realization of viable neutrino mass matrices with two texture zeros [24][25][26][27][28][29], 1 using symmetry arguments [34], requires two or three scalar triplets [35]. In this paper, we take up the case of two coexisting triplets.…”
Section: Jhep02(2014)060mentioning
confidence: 99%
“…Apart from being interesting in itself, several scalar triplets naturally occur in models for neutrino masses and lepton mixing based on the type II seesaw mechanism. In particular, it has been shown that in such a scenario a realization of viable neutrino mass matrices with two texture zeros [24][25][26][27][28][29], 1 using symmetry arguments [34], requires two or three scalar triplets [35]. In this paper, we take up the case of two coexisting triplets.…”
Section: Jhep02(2014)060mentioning
confidence: 99%
“…[25,33] discuss gauged U(1) L μ −L τ models where neutrino masses are radiatively induced at one-loop level. It turns out that the neutrino-mass matrices in these models have the form of the two-zero texture [62][63][64][65][66], which predicts IO for neutrino-mass spectrum. Thus, the determination of neutrino-mass hierarchy in future neutrino experiments allows us to distinguish this class of models from the minimal model, where NO is predicted as we have seen above.…”
Section: Introductionmentioning
confidence: 99%
“…Our approach is a combination of two very different approaches to lepton flavor: (a) texture-zeros that increase predictivity and relate mixing angles with masses [26][27][28][29][30] and (b) symmetries that fully or partly determine the mixing structure independently of the masses [10,11,31]. The former usually requires abelian symmetries [32] while the latter requires nonabelian discrete symmetries [10,11].…”
Section: Introductionmentioning
confidence: 99%